2020
DOI: 10.1016/j.heliyon.2020.e04779
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol enhances PGF2α-stimulated osteoprotegerin synthesis in osteoblasts

Abstract: Osteoprotegerin (OPG) synthesized by osteoblasts is currently considered a crucial regulator to suppress the formation and function of osteoclasts. We previously showed that the synthesis of OPG is stimulated by prostaglandin F 2α (PGF 2α ) in the involvement of p38 mitogen-activated protein kinase (MAPK), stress-activated protein kinase/c- Jun N-terminal kinase (SAPK/JNK) and p44/p42 MAPK in osteoblast-like MC3T3-E1 cells. We also found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies have shown that PGF2α can activate the MAPK signaling pathway after coupling with the FPR [ 24 , 25 ]. MAPK signaling regulates various biological activities, among which ERK activation is crucial during the early stage of adipogenesis and is essential for PPARγ transcription [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PGF2α can activate the MAPK signaling pathway after coupling with the FPR [ 24 , 25 ]. MAPK signaling regulates various biological activities, among which ERK activation is crucial during the early stage of adipogenesis and is essential for PPARγ transcription [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…tivities in osteoblast-like MC3T3-E1 cells (Kim et al 2020). Thus, the effects of analgesic agents on the osteoprotegerin synthesis in osteoblasts might be quite different in each other.…”
Section: Effects Of Sp600125 On the Expression Levels Of Osteoprotege...mentioning
confidence: 99%